Impacts of consumers' electricity price misperceptions - Martin Baikowski (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2018)
Empirical findings indicate that a large share of households misperceives electricity prices and is not able to make deliberate choices in energy service consumption, which leads to biased consumption decisions and thus to inefficient energy use. To investigate the impact of misperceived electricity prices on the derived demand for electricity, the economy and domestic CO2 emissions, we make use of a computable general equilibrium (CGE) model. The model allows us to take the narrow interweaving of production and consumption sectors into account to investigate the repercussions on supply and demand in Germany and Europe. Providing information on electricity prices or the most efficient utilisation can stimulate reductions in electricity consumption if households are aware of possible trade-offs. However, if consumers perceive the electricity price to be much higher than it actually is, providing information on the true electricity price might turn out to be counter-productive in terms of electricity consumption and domestic CO2 emissions.
Keywords: D58; Q41; Q43; 330; residential energy consumption; energy efficiency; behavioural inefficiency; electricity price misperception; consumer inattention